Hospitals with Briefer than Average Lengths of Stays for Common Surgical Procedures Do Not Have Greater Odds of Either Re-Admission Or Use of Short-Term Care Facilities. Issue 2 (March 2017) - Dexter, F.; Epstein, R. H.; Dexter, E. U.; Lubarsky, D. A.; Sun, E. C.
We considered whether senior hospital managers and department chairs need to be concerned that small reductions in average hospital length of stay (LOS) may be associated with greater rates of re-admission, use of home health care, and/or transfers to short-term care facilities. The 2013 United States Nationwide Readmissions Database was used to study surgical Diagnosis Related Groups (DRG) with 1) national median LOS ≥3 days and 2) ≥10 hospitals in the database that each had ≥100 discharges for the DRG. Dependent variables were considered individually: 1) re-admission within 30 days of discharge, 2) discharge disposition to home health care, and/or 3) discharge disposition of transfer to short-term care facility (i.e., inpatient rehabilitation hospital or skilled nursing facility). While controlling for DRG, each one-day decrease in hospital median LOS was associated with an odds of re-admission nationwide of 0.95 (95% confidence interval [CI] 0.92–0.99; P=0.012), odds of disposition upon discharge being home care of 0.95 (95% CI 0.83–1.10; P=0.64), and odds of transfer to short-term care facility of 0.68 (95% CI 0.54–0.85; P=0.0008). Results were insensitive to the addition of patient-specific data. In the USA, patients at hospitals with briefer median LOS across multiple common surgical procedures did not have a greater risk for either hospital re-admission within 30 days of discharge or transfer to an inpatient rehabilitation hospital or a skilled nursing facility. The generalisable implication is that, across many surgical procedures, DRG-based financial incentives to shorten hospital stays seem not to influence post–acute care decisions.